IMPLEMENTATION OF VOICE RECOGNITION TECHNOLOGY ON ENGLISH LEARNING APPLICATION BY SELF LEARNING BASED ON ANDROID DEVICE - Derwin Suhartono; Calvin Calvin; Mery Yustina; Shandy Kurniawati; Haryono Soeparno; Fredy Purnomo (Prosiding SNST Fakultas Teknik, 2013)
Nowadays, English is going global; it has forced almost all parts of the world to use English as the main communication language. The growth of media needs to learn English is also run rapidly. This prompted the need of many tools or media that can be used as a tool to learn English well. In this research, the application development as a learning device for self-learning using Android is done by embedding voice recognition technology in it. The method used here is embedded speech recognition method. Embedded speech recognition method is often used in mobile application and it is simpler than either network speech recognition or distributed speech recognition. This is due to the lack of signal transmission from the client to the remote server. The application is developed to support English learning especially for listening and speaking. Keywords: Android, English, Self Learning, Voice Recognition